Incidental emotions have a greater impact on the logicality of less proficient reasoners. (2nd January 2017) - Blanchette, Isabelle; Nougarou, François
ABSTRACT: Previous research shows differences in reasoning about emotional and neutral stimuli. A common explanation hypothesised for this effect is that emotion incurs an additional cognitive load. If this is the case, incidental emotion should have a greater impact on the reasoning of less proficient reasoners, and when items are more difficult, because a greater proportion of available cognitive resources must be allocated to the task. We manipulated the emotional value of reasoning stimuli using conditioning and with the simultaneous presentation of images. The deleterious effect of emotion on logicality was greater for less proficient reasoners. There was also some indication that the effect of emotion may be more pronounced for more difficult items. Physiological responses and affective evaluations of the stimuli were similar across groups, irrespective of reasoning proficiency. Results provide some support for the hypothesis that the impact of emotion occurs through increased cognitive load.